2020
DOI: 10.1097/gox.0000000000002969
|View full text |Cite
|
Sign up to set email alerts
|

Education during Surgical Outreach Trips in Vietnam: A Qualitative Study of Surgeon Learners

Abstract: Background: Visiting educator trips teach surgical care in low-resource settings to develop sustainable global surgery. Surgery has been integral in these volunteer activities, but it is unknown whether surgeon learners receive suitable education during these trips. We sought to describe the educational experiences of surgeon learners during a visiting educator trip to better understand the perceptions of surgical outreach education. Methods: We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Twenty-five studies (83%) described advantages with visiting surgical teams,17 19–42 further subgrouped into skills improvement, immediate clinical patient care, system-level strengthening, academic and career benefits and broader collaboration opportunities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-five studies (83%) described advantages with visiting surgical teams,17 19–42 further subgrouped into skills improvement, immediate clinical patient care, system-level strengthening, academic and career benefits and broader collaboration opportunities.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most reported benefits of visiting surgical teams related to skill transfers (n=16, 53%)19–22 24–27 30 32–38 including both surgical techniques of advanced procedures, non-technical skills including ‘personal professionalism’, decision-making and a positive ‘cultural change’,19 22 25 26 31 which was emphasised by an attending surgeon in Ethiopia:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, identification of hand educational needs and surgical capacity are essential steps to decreasing the risk of dependency on visiting educators or high-volume mission trips, building local infrastructure, and transitioning surgical care to a system that is completely directed by locals. 2,18 A recent study 49e demonstrated that the quality and quantity of educational materials in low-and middle-income countries are lacking 19 ; information garnered from this assessment tool can help curate selfdirected learning, didactic webinars, virtual case reviews, discussion boards, instructional operative videos, and relevant research articles. 3,12,20 In addition, future research should further assess how to effectively deliver surgical and trauma-related education in-person and over a virtual platform to ensure that contextualized learning occurs yearround in an uninterrupted manner.…”
Section: Ementioning
confidence: 99%